Vitamin D Deficiency in Iraqi Women with Hashimoto Thyroiditis - Ali Mohamed, Kalaweesh; Khorshid Abbas, Sahlah (Tikrit Journal of Pure Science, 2025)
One kind of autoimmune thyroid disease is Hashimoto's thyroiditis (HT), which is more frequent in women than in males. The purpose of our study was to demonstrate any possible variations in vitamin D levels between ladies with HT and healthy women. METHODS: Fifty healthy Individuals (HI) and fifty HT patients made up the research group of 100 volunteers. Anti-thyroid peroxidase antibody (TPO-Ab) and anti-thyroglobulin antibody (Tg-Ab) levels were used to diagnose HT. The amounts of thyroid-stimulating hormone (TSH), free thyroxin (fT4), free triiodothyronine (fT3) and Vitamin D (Vit-D) were also assessed. RESULTS: In comparison to the HI, the patients' levels of anti-TPO, anti-TG and TSH were considerably greater, with an overall decrease in vitamin D levels in the three categories Vit-D < 20 (Deficiency), Vit-D 20–30 (Insufficiency) and Vit-D > 30 (Sufficiency). Furthermore, there was a significant increase in anti-TPO levels in patients compared to HI in all categories. This study also found a significant positive association between the anti-TPO and TSH levels in HT patients whose serum vitamin D level was more than 30 and a negative correlation between the levels of TSH and fT3 in HT patients whose serum vitamin D level was less than 20. CONCLUSIONS: A lower 25(OH)D level is seen in HT patients, and TSH is a separate risk factor for HT. Additionally, a significant increase in anti-TPO levels was observed overall and in the categories (deficient, insufficient, and sufficient) in women with HT.